Usefulness of C-reactive protein-triglyceride glucose index in detecting prevalent coronary heart disease: findings from the National Health and Nutrition Examination Survey 1999–2018 - Xu, Ming; Zhang, Lingyun; Xu, Dong; Shi, Wenrui; Zhang, Weiguo (Frontiers in Cardiovascular Medicine, 2024)
Background Coronary heart disease (CHD) is one of the leading causes of mortality. The current study aims to assess the association between C-reactive protein-triglyceride glucose index (CTI) and the risk of prevalent CHD and to evaluate the usefulness of CTI to refine the identification of prevalent CHD. Methods 19,451 subjects from the National Health and Nutrition Examination Survey 1999–2010 were enrolled. CHD was ascertained according to the questionnaire. Results The prevalent of CHD was 6.23%. After adjusting for conventional cardiovascular risk factors, each SD increase of CTI could cast a 1.357 times risk of CHD. In quartile analysis, the top quartile had a 1.807 times risk of CHD than the bottom quartile. Smooth curving fitting displayed that the association was linear in the entire range of CTI. Subgroup analysis revealed that the association was robust among several common subpopulations but stronger in subjects aged <60. Finally, both ROC and reclassification analysis demonstrated a significant improvement in identifying CHD when introducing CTI to the Framingham risk score. Conclusion CTI has a positive, linear, and robust association with prevalent CHD in the general American population, and CTI may help to improve the detection of prevalent CHD in the general population.